Association between belief in medicine and adherence to antiretroviral therapy among human immunodeficiency virus adults in Zaira, Kaduna State, Nigeria - Eze, Rosemary A; Sulaiman, Norhasmah; Mat Daud, Zulfitri 'Azuan; Babadoko, Aliyu (Springer Science and Business Media LLC, 2023)
Background: Negative perceptions of antiretroviral treatment (ART)'s efficacy and consequences may operate as roadblocks to adherence. This research aimed to determine the association between belief in medicine and adherence to antiretroviral therapy among HIV adults on ART in Ahmadu Bello University Teaching Hospital, Zaria, Kaduna State, Nigeria. Method: Using a cross-sectional design, a systematic random sampling method was used to select respondents aged 18-64 years on antiretroviral therapy for at least six months at Ahmadu Bello University Teaching Hospital, outpatients of the President's Emergency Plan for AIDS Relief Clinic. Sociodemographics, belief in medicine and adherence to ART were obtained using a self-administered questionnaire. Descriptive statistics, chi-square test, and multiple logistic regression were used for data analysis. Results: Among the 385 people who took part in the study, about 67.5 were females and 32.5 were males. About 54 of adults adhered to ART. More than half (55.8) of the respondents had negative perceptions (beliefs) of personal need for ART medication and about 42.3 of the respondents had more concerns about the potential negative effects of the ART medication. Government employment (odds ratio (OR) = 2.842, p =